Exercise Prescription in Arrhythmogenic Cardiomyopathy: Finding the Right Balance Between Risks and Benefits - Lorenzo‐Lupo Dei; Jennie Han; Silvio Romano; Luigi Sciarra; Angeliki Asimaki; Michael Papadakis; Sanjay Sharma; Gherardo Finocchiaro (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2025)
Arrhythmogenic cardiomyopathy (ACM) is an inherited cardiac condition, often caused by mutations in genes encoding desmosomal proteins. The pathologic hallmark of the disease is a fibrofatty replacement of the myocardium, which constitutes the substrate for potentially fatal ventricular arrhythmias. ACM is one of the most common etiology of sudden cardiac death in athletes and young individuals. Although it is well established that regular exercise confers multiple health benefits and better survival in the general population, intense exercise may accelerate the phenotypic expression and the propensity to ventricular arrhythmias in patients with ACM. This review discusses current evidence regarding the safety and the effects of exercise in ACM. We scrutinize research findings based on animal and human models that raise concerns on the possible detrimental role of intense exercise in this condition. Finally, we examine the current knowledge on exercise prescription focusing on the optimal amount of exercise that should be recommended to patients with ACM.